2014
DOI: 10.1021/bm501266x
|View full text |Cite
|
Sign up to set email alerts
|

Translocation and Induced Permeability of Random Amphiphilic Copolymers Interacting with Lipid Bilayer Membranes

Abstract: We investigate adsorption and passive translocation of random amphiphilic copolymers interacting with a self-assembled lipid bilayer membrane. By using the bond fluctuation model with explicit solvent, we consider random copolymers under variation of the fraction, H̅, of hydrophobic sites and chain length. Our results indicate a point of balanced hydrophobicity, where a slight excess of hydrophobic monomers compensates an additional insertion barrier due to the self-organized packing of the bilayer. Close to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 55 publications
11
55
0
Order By: Relevance
“…Here, Z is an average coordination number taken from the simulations (Z ≈ 4−7, depending on H B ), ϵ 0 = 0.8k B T the energy scale as before, and μ ins ≈ 0.9k B T 27,29,33. …”
mentioning
confidence: 99%
“…Here, Z is an average coordination number taken from the simulations (Z ≈ 4−7, depending on H B ), ϵ 0 = 0.8k B T the energy scale as before, and μ ins ≈ 0.9k B T 27,29,33. …”
mentioning
confidence: 99%
“…Previous simulation studies on linear homopolymers 45,46 and amphiphilic copolymers 56 showed that a polymer suppresses permeability when fully embedded in the bilayer's core in the limit large hydrophobicity. Experimental data on PP50, however, indicate that full insertion of amphiphilic branched polymer is not necessary for suppression of permeability, if anchoring side groups are sufficiently hydrophobic.…”
Section: Coarse Grained Monte Carlo Simulationmentioning
confidence: 99%
“…By decreasing the value of H to H = 0.8, the hydrophobicity of the side chains gets close to a point of balanced hydrophobicity, where a polymer-induced increase of permeability has been seen for homopolymers 45,46 as well as random amphiphilic copolymers. 56…”
Section: Coarse Grained Monte Carlo Simulationmentioning
confidence: 99%
“…As the interior region of the phospholipid bilayer membrane is hydrophobic, hydrophilic molecules do not readily cross cell membranes [24][25][26]. Due to this property, an electron mediator must have sufficient hydrophobicity to permeate cell membranes [15,27].…”
Section: 1 Characterization Of Pmfcsmentioning
confidence: 99%